'Closed-loop supply chain models with bundling strategy'. Issue 6 (2nd November 2021) - Jena, Sarat Kumar
ABSTRACT: In recent decades, due to the resulting competitive situation between new and refurbished products, the bundling tactics of closed-loop supply chain (CLSCs) is closely related to the marketing strategies adopted by the competitive channels. Despite this practice, there is little understanding on how exactly bundling strategies impact CLSCs' profits under a competitive environment. Therefore, this study made a major contribution by incorporating both bundling (mixed bundling and pure bundling) and collection strategies under price competition, into a game-theoretic model of CLSCs, where re-furbished products are packaged with new products by the retailer in a bundle. To analyse the bundling effect, mathematical models are developed under direct and indirect collection processes, and numerical analysis is presented. Results of the proposed model show that the total supply chain profit is higher in mixed bundling compared to pure bundling. Furthermore, it is observed that the direct collection strategy generates maximum profit in mixed bundling, while the indirect collection strategy yields higher profit in pure bundling. The results also show that under lower refurbished product's market size, a pure bundling strategy would be helpful to increase the profit of the manufacturer and the retailer.